A Feminist Stylistic Analysis of Linguistic Resistance in Gloria Gaynor’s "I Will Survive" - Br. Sitorus, Rosalyn Magdalena; Ginting, Valencia Laurence; Fitriana, Fadila; Alfian, Alvin; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
Music is an art form that mirrors social and cultural realities. Gloria Gaynor's iconic song "I Will Survive" is recognized as a symbol of female empowerment. This study aims to investigate how linguistic features in the song portray women's strength and resistance against patriarchal norms, using Sara Mills' feminist stylistics framework. Employing qualitative textual analysis, the study focuses on identifying specific linguistic elements—such as powerful verbs, assertive pronouns, and repetition—that contribute to constructing a narrative of female independence. The findings reveal that "I Will Survive" functions as a textual act of resistance, reshaping the portrayal of women in popular media. This study contributes to feminist discourse by demonstrating how language choices in popular music challenge gender stereotypes and promote ideological empowerment.